Applying Fuzzy cluster index to improve searching in data warehouse - Mohammed, Ahmad Abdullah; Guirguis, Shawkat Kamal; Madbouly, Magda Mohamed (Discoveries in Agriculture and Food Sciences, 2015)
Data Warehouse (DW) is one of the solutions for decision-making process in a business organization. But it only stores data for managerial purpose and it has no intelligent mechanism for decision making. For improving the process of decision making and searching Data Warehouse (DW) of the medical resources (items), where this study includes an application on a Data Warehouse (DW) of medical resources (items).In this paper, we merged the fuzzy rule with cluster index technique. where The proposed technique is named Fuzzy Cluster Index technique (FCI) to improve and speed up Queries fuzzy rule and process of decision making and management medical (items), The performance evaluation of three data warehouse queries is focused in this paper by comparing with Fuzzy cluster index technique (FCI), Fuzzy Rule and Index-based Apriori Algorithm to observe the results of variable size dataset with respect to time. Eventually, the designed system was constructed and executed by using (C# version 2010) which is a visual and object oriented programming language. This proves the efficiency of the proposed system for improving searching in Data Warehouse (DW) and the decision support system for the medical items in a perfect way.